2013
DOI: 10.1017/s0022215113000108
|View full text |Cite
|
Sign up to set email alerts
|

Day-case tonsillectomy for children in Glasgow: the impact of changing indications and deprivation

Abstract: Eligibility for tonsillectomy with same day discharge has increased. This appears to be related to an increase in the number of children who are able to fulfil the social criteria for same day discharge. The results indicate an association between deprivation and tonsillectomy, particularly surgery carried out for the symptoms of sleep-related breathing disorders or obstructive sleep apnoea hypopnoea syndrome. There has been a significant increase in the percentage of children undergoing tonsillectomy for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Our findings flank the proportion observed in a UK national audit of 33% among children aged <5 years in 2003/4 [27]. The rise is also consistent with a Scottish study, which reported ambulatory (adeno)tonsillectomies in children for the SDB spectrum increased from 26% to 55%, between 2001 and 2011, respectively, and SDB was the most common indication for (adeno)tonsillectomy among pre-school children (aged <5 years) [9]. A likely explanation is that this is a consequence of increased awareness and diagnostic rates of SDB among family practitioners and otolaryngologists [28] [29].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings flank the proportion observed in a UK national audit of 33% among children aged <5 years in 2003/4 [27]. The rise is also consistent with a Scottish study, which reported ambulatory (adeno)tonsillectomies in children for the SDB spectrum increased from 26% to 55%, between 2001 and 2011, respectively, and SDB was the most common indication for (adeno)tonsillectomy among pre-school children (aged <5 years) [9]. A likely explanation is that this is a consequence of increased awareness and diagnostic rates of SDB among family practitioners and otolaryngologists [28] [29].…”
Section: Discussionsupporting
confidence: 91%
“…In the US, there has been a shift towards performing (adeno)tonsillectomy in younger children and an increasing number of pre-school children have undergone surgery for the SDB spectrum over recent years with low complication rates [7], [8]. A small number of studies and reviews suggest similar trends have occurred in the UK and other European countries and are consistent with evidence of increased awareness, diagnosis and surgical intervention for the SDB spectrum [9] [10]. A small Scottish study found an association between deprivation and (adeno)tonsillectomy, particularly operations performed for symptoms related to SDB or OSAS [9], whilst a Canadian observational study of children with and without OSAS, found that those with OSAS were more likely to reside in disadvantaged areas [11].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Encouragingly, improved social deprivation scores also contributed significantly to an increase in the local day-case rate, from 27 per cent in 2001 to 42 per cent in 2011. 6 We are still doing some good. The challenge remains to convince those holding the purse strings.…”
mentioning
confidence: 98%